The Technical Capacity of Jetty Structure Analysis of The Lampia Port - Paotonan, Chairul; Rahman, Sabaruddin; Mas’ud M, Ahmad Azwar; Putra, Teguh Pairunan (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
PT. Sinergi Perkebunan Nusantara plans to use the Lampia port for shipping of Crude Palm Oil (CPO). Lampia Jetty has more than ten years old so that its carrying capacity against external loads may have decreased. Therefore for the operational safety of the ship, it is necessary to study the engineering capacity of the pier. By knowing the engineering capacity of the existing pier, the maximum ship dimensions that can be served by pier can be determined. This study began with the collection of supporting data consisting of ship data, hydro-oceanographic data, bathymetry data, pier structure data and earthquake data. Furthermore, the load calculation that works on the pier consists of dead and live loads, earthquake loads, ship impact loads, current loads, wave loads, ship tensile loads and wind loads. After the load calculation is completed, then the pier modeling is done using SAP2000 software followed by inputting the load using a specific combination of loading and running model. In this study the dimensions of the ship were varied namely 500 ton, 700 ton, 1000 ton, 2000 ton and 3000 ton. The indicator used in assessing the technical capacity of the pier is the safety factor (SF) as a function of the ship DWT. Based on the results of the strength analysis of the pier structure, it was found that the existing pier is capable and safe serving ships with a size of 27 1027 DWT if it uses a safety factor (SF) 1.5. Whereas if use the safety factor (SF) 2.0, the existing pier structure is capable and safe to service ships with a size of ≤ 510 DWT.